2019
DOI: 10.5530/jyp.2019.11.81
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Effect of Heat Therapy on Osteoblasts Growth and Differentiation Following Treatment with Bone Antiresorptive Drugs- An in vitro Study

Abstract: Objectives: To find out the effect of mild heat shock on osteoblast proliferation and mineralisation following treatment with bisphosphonates. Materials and Methods: Cell culture of MC3T3 cells was performed in alpha minimum essential medium supplemented with 10% Foetal Calf Serum (FCS), 2 mmol L-glutamine and 100U/ml each of penicillin/streptomycin and were incubated at 37°C in humidified 5% CO 2. The selected bisphosphonate drugs were administered, following which heat therapy was given by placing the flasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“… 252 Various in vitro and in vivo studies have indicated the therapeutic and anticancer effects of water bath heat treatment (as a kind of whole-body hyperthermia treatments) for example at 43.5 °C and 45 °C (30 min), 254 47 °C and 37 °C (1 min heat shock), 255 37, 39, and 37 °C (24-hr). 256 As a novel option for cancer patients, combining hyperthermia and chemotherapy at considerably reduced-drug doses can indicate an exceptional efficacy, for example, therapy of breast cancer 249 and ovarian cancer 257 . Further, clinical experiences have indicated a combination treatment of radiotherapy with chemotherapy as a desired therapy for superficial tumors, including skin carcinomas, Merkel cell carcinoma, and malignant melanoma.…”
Section: Studying the Methods Used In The Hyperthermia And Cancer Tre...mentioning
confidence: 99%
“… 252 Various in vitro and in vivo studies have indicated the therapeutic and anticancer effects of water bath heat treatment (as a kind of whole-body hyperthermia treatments) for example at 43.5 °C and 45 °C (30 min), 254 47 °C and 37 °C (1 min heat shock), 255 37, 39, and 37 °C (24-hr). 256 As a novel option for cancer patients, combining hyperthermia and chemotherapy at considerably reduced-drug doses can indicate an exceptional efficacy, for example, therapy of breast cancer 249 and ovarian cancer 257 . Further, clinical experiences have indicated a combination treatment of radiotherapy with chemotherapy as a desired therapy for superficial tumors, including skin carcinomas, Merkel cell carcinoma, and malignant melanoma.…”
Section: Studying the Methods Used In The Hyperthermia And Cancer Tre...mentioning
confidence: 99%
“…Although biochemical induction factors are widely used to create ECM-like microenvironments, nowadays, growing studies report significant contributions of biophysical inducers in TE. There are numerous reports about the effects of heat, [219][220][221] ultrasound waves, 222 magnetic fields, 223 electrical, [224][225][226] mechanical, [227][228][229] and light stimulation on cellular phenotype and function. 230,231 Furthermore, different topographical aspects of the matrix, such as surface stiffness, elasticity, and porosity, could be considered as inductive factors to modify cell fate determination.…”
Section: Biophysical Factorsmentioning
confidence: 99%